2013
DOI: 10.1002/app.39338
|View full text |Cite
|
Sign up to set email alerts
|

Bulk synthesis of homogeneous and transparent bulk core/multishell quantum dots/PMMA nanocomposites with bright luminescence

Abstract: Core/multishell CdSe/CdS/CdS/Cd0.75Zn0.25S/Cd0.5Zn0.5S/Cd0.25 Zn0.75S/ZnS/ZnS QDs/PMMA bulk nanocomposites were successfully synthesized. To achieve a homogeneous and stable dispersion in MMA monomers, QDs were first modified with amphiphilic polymer of poly(ethylene glycol)‐oleate (PEG‐oleate). Subsequently, the transparent and homogeneous bulk composites were obtained by photopolymerization. The TEM analysis of ultramicrotome cut of composite demonstrates that QDs are well dispersed in the PMMA matrix. UV–vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The first synthesis of multilayered QDs was reported by Shi and co-workers, 201 subsequently followed by several synthetic strategies for preparing multishell QDs. 203 In their synthetic scheme, the authors reported modification of the QDs with the amphiphilic polymer poly(ethylene glycol)-oleate (PEG-oleate) in order to make a homogeneous dispersion. 202 A more complex CdSe/CdS/CdS/Cd 0.75 Zn 0.25 S/Cd 0.5 Zn 0.5 S/Cd 0.25 Zn 0.75 S/ZnS/ZnSQDs/ PMMA bulk nanocomposite has been synthesized using a combination of SILAR method (to prepare layered QDs) and photopolymerization (to synthesize the outer organic shell) using 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) as the initiator (Fig.…”
Section: Synthesis Of Core-shell Nanocatalystsmentioning
confidence: 99%
“…The first synthesis of multilayered QDs was reported by Shi and co-workers, 201 subsequently followed by several synthetic strategies for preparing multishell QDs. 203 In their synthetic scheme, the authors reported modification of the QDs with the amphiphilic polymer poly(ethylene glycol)-oleate (PEG-oleate) in order to make a homogeneous dispersion. 202 A more complex CdSe/CdS/CdS/Cd 0.75 Zn 0.25 S/Cd 0.5 Zn 0.5 S/Cd 0.25 Zn 0.75 S/ZnS/ZnSQDs/ PMMA bulk nanocomposite has been synthesized using a combination of SILAR method (to prepare layered QDs) and photopolymerization (to synthesize the outer organic shell) using 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO) as the initiator (Fig.…”
Section: Synthesis Of Core-shell Nanocatalystsmentioning
confidence: 99%
“…The thermal stability of PMMA-SH/CdSe@CdS QDs is better than that of the bare PMMA-SH lm aer 340 C. The improvement of the thermal stability of the PMMA-SH/CdSe@CdS QDs nanocomposite could be assigned to the interaction between the CdSe@CdS QDs and PMMA-SH polymer chains. 50 The further crosslinking in the PMMA-SH/CdSe@CdS QDs nanocomposite hindered the movement of the PMMA-SH chains and prevented its thermal decomposition. The superior thermal stability of the PMMA/ QDs nanocomposite is of great importance for applications in device manufacturing.…”
Section: Transparent and Thermal Properties Of The Pmma-sh/ Cdse@cds ...mentioning
confidence: 99%
“…be seen in Table 2, at low addition ratios (0.2% and 1%), nanocomposites show close thermal stability to LDPE. However, the sample with 5% CdSe addition showed faster degradation than the others [18,19]. The TEM image of CdSe QD revealed a distinct spherical shape pattern of the particle distribution and also showed that the particles were highly monodispersed and the CdSe QD measured was 2.8 nm.…”
mentioning
confidence: 93%